2016
DOI: 10.1017/aae.2016.8
|View full text |Cite
|
Sign up to set email alerts
|

Mean-Variance Versus Mean–expected Shortfall Models: An Application to Wheat Variety Selection

Abstract: Abstract.One of the most popular risk management strategies for wheat producers is varietal diversification. Previous studies proposed a mean-variance model as a tool to optimally select wheat varieties. However, this study suggests that the mean-expected shortfall (ES) model (which is based on a downside risk measure) may be a better tool because variance is not a correct risk measure when the distribution of wheat variety yields is multivariate nonnormal. Results based on data from Texas Blacklands confirm o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Results can, therefore, be directly translated into actionable information for climate adaptation on the ground. The findings can serve to create variety portfolios that diminish climate risk ( 22 ), can feed into climate information services in combination with seasonal forecasts ( 28 ), and can become part of decentralized plant breeding strategies for climate adaptation ( 8 ). Combining the tricot trial data with other data could generate additional insights into variety performance and acceptability as influenced by environmental ( 11 ), socioeconomic ( 29 ), and genomic ( 30 ) factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results can, therefore, be directly translated into actionable information for climate adaptation on the ground. The findings can serve to create variety portfolios that diminish climate risk ( 22 ), can feed into climate information services in combination with seasonal forecasts ( 28 ), and can become part of decentralized plant breeding strategies for climate adaptation ( 8 ). Combining the tricot trial data with other data could generate additional insights into variety performance and acceptability as influenced by environmental ( 11 ), socioeconomic ( 29 ), and genomic ( 30 ) factors.…”
Section: Discussionmentioning
confidence: 99%
“…These two metrics produced divergent variety recommendations in all three cases (indicated in bold in Table 3 ). In principle, risk analysis for variety choice is also possible without explicit climatic analysis, but this produces results that are difficult to interpret in terms of climatic causality and requires trials during a large number of seasons to avoid sampling bias and to characterize probability distributions accurately ( 22 ).…”
Section: Improving Variety Recommendationsmentioning
confidence: 99%
“…The evaluations mentioned above focus on average performance of varieties, but other approaches focus on the variation in performance across seasons to assess farmers’ risks. It has been shown that multi-environmental trial data from several seasons can be used to propose variety portfolios to reduce risk and maximize farmers’ profits (Nalley et al 2009 ; Nalley and Barkley 2010 ; Sukcharoen and Leatham 2016 ). These studies all focus on yield as the main evaluation criterion.…”
Section: Analysis Of Different Types Of Datamentioning
confidence: 99%
“…"coherent" state-of-the-art risk metric in finance [29,30], which has already been applied in agriculture to generate variety portfolio recommendations [31].…”
Section: Potential Contribution Of the Minimum Regret Modelmentioning
confidence: 99%